The proposed action of styrylpyrone derivative in hsv-1 infected vero cells by differential gene expression - Noor Zarina, Abd Wahab; Nazlina, Ibrahim; Halimah, Abdullah Sani; AzimahtolHawariah, Lope Pihie (2015)
This study was done to identify and characterize specific cellular genes expression during infection of host with HSV1 and treatment with styrylpyrone derivative (SPD). SPD showed antiviral activity with different modes of action against HSV1. SPD was effective in inhibiting cell death when the substance was added at 2 hours to 4 hours post infection. Cell death was only observed when treatment was delayed to 5 and 6 hours post infection. Positive effect to this mode of action suggests that SPD were able to treat HSV1 infected cells at two effective concentration of 1.563x107 µM and 7.813x108 µM in treatment mode [S+V]+SPD. Differential gene expression (DEG) method was used to determine and isolate the genes that are differentially expressed in HSV1 infected Vero cells with and without treatment with SPD. Results from DEG analysis showed that a total of 177 genes were expressed differentially with 89 cDNAs candidates were induced and 88 cDNAs candidates were repressed. All the genes were determined by their nucleotide sequences that were compared with the database from Genbank via bioinformatic analysis. Eight markers from DEG analysis were chosen and their expressions were confirmed by using RealTime PCR. Results from RealTime PCR showed 100% correlation in the markers’ expression profile showed by DEG method. The cDNA markers that were induced in their expression include mitogenactivated protein kinase, tapasin, carboxypeptidase M, RAB member RAS oncogen family, p53and G proteincoupled receptor. We found that SPD induced apoptosis, as measured by oncogene family gene expression and caspase activation. The apoptosis mediated by SPD in infected cells was associated with the activation of p53 and Bcl2 protein via intrinsic pathway. SPD also exerts its antiHSV1 properties by activating an extrinsic pathway via caspase8 activation in infected cells. From this study, the understanding on how SPD acted upon HSV1 infected host cells during the infection process was proposed. In this study it was shown that SPD has a potential in controlling HSV1 infection selectively without disturbing noninfected cells.